Analysis of MSME Empowerment in MSMEs Assisted by PT Pegadaian Regional Office VIII Jakarta - Yuka Maylinda Hidayah; Wiradendi Wolor, Christian; Marsofiyati, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
In the midst of increasingly fierce economic and business competition empowering Micro, Small and Medium Enterprises (MSMEs) is an important strategy to improve the competitiveness and sustainability of the MSME sector. This study aims to determine and analyze the MSME empowerment program carried out by PT Pegadaian Regional Office VIII Jakarta. Specifically, this research wants to understand the implementation of the program, the benefits felt by MSMEs after participating in the program, and the changes that occur in MSME actors. The method used in this research is qualitative with a descriptive approach. Data were obtained from direct observation, interviews, literature studies, and documentation on MSMEs involved in the empowerment program. The results showed that this program was very beneficial for the MSMEs involved. Some MSME players felt significant changes, such as an increase in the number of customers and income after participating in the program. However, this study also found that there are still some PT Pegadaian branches included in region VIII Jakarta that have not fully contributed to this empowerment program. These findings indicate the need for further efforts, so that the MSME empowerment program can have a broader and more sustainable impact across the region.